2022-RA-778-ESGO Rare gynecological cancers in a gynecologic cancer center: 11-year experience of KEM. (20th October 2022) - Moubarak, Malak; Ataseven, Beyhan; Heitz, Florian; Welz, Julia; Baran, Burcu; Pauly, Nina; Kaiser, Sabrina; Westermann, Timo; Traut, Alexander; Bois, Andreas du; Harter, Philipp
Abstract : Introduction/Background: Many gynecologic cancers fulfill the criteria of a rare tumor with an annual incidence of <6 per 100, 000 women. As these tumor entities are difficult to treat, specialized knowledge and skills are necessary. We analyzed the 11-year experience with rare tumors in a tertiary gynecologic oncology center. Methodology: All consecutive patients with rare gynecological cancers treated at our department between 2011 and 2021 were included. Results: 1, 460 patients with a rare gynecologic cancer entered our department. 1, 092 patients received any kind of therapy and 368 'only' had a consultation. The most common histologic types were: borderline tumors of the ovary (424 pts, 29%), low grade serous ovarian cancer (179 pts, 12.3%), ovarian sex cord-stromal tumors (164 pts, 11.2%), uterine sarcoma (142 pts, 10%), clear cell ovarian cancer (115 pts, 8%), and ovarian germ cell tumors (73 pts, 5%). There was a continuous increase of pts over the years: 237 (2011–2013), 215 (2014–2015), 276 (2016–2017), 347 (2018–2019), 385 (2020–2021) cases. In total, 905 pts came from NRW and 555 patients from other states. Conclusion: We observe a centralization of patients from whole Germany with rare gynecological cancers in our center with a rising number of patients during the observation period. This provides a unique chance for further research in rare gynecologic tumors and also allows to offer prospective trials.